Lyricism Of K. G. Paustovsky As The Main Artistic Intention Of 1940-1945 - Maxmudova Marina Vladimirovna (Western European Studies, 2024)
The article, based on the story “Nastya the Lacemaker,” analyzes the work of Konstantin Georgievich Paustovsky during the Great Patriotic War (1940-1945). Particular attention is paid to the lyrical direction in his works, which became the main artistic vector of the writer in those years. The author of the article explores how, during the war, Paustovsky was able to preserve and develop the lyrical potential of his talent, despite ideological pressure and restrictions
Keywords: Lyricism; intention; microprose